THE ADMINISTRATION OF COLLEGE COURSES IN ACCOUNTING. - Chapman, H. H. (The Accounting Review, 1926)
Abstract As a group, teachers of accounting have contributed largely to the literature of accounting in the way of general treatises and of special studies on particular phases of the subject, but, in so far as published material may he taken as evidence, have given comparatively little attention to the problems which arise in the teaching of accounting. It is true that at least one institution gives a course in the college curriculum in accounting for six weeks during the summer and that a number of articles have been published on one phase or another of college courses. The material, however, is scanty at best, and the writer does riot know of any attempt to give a complete statement of the problems which confront the head of an accounting department in a collegiate school of business. The present paper, however, is not concerned especially with discussing the problems of the individual teacher, but it is designed to raise the question of the responsibilities of the head of a department of accounting in directing the instructional work of his department. The writer feels that the department head should take an active part in planning the courses, in encouraging and aiding his instructors to do their best work, and in providing conditions which will pave the way for effective teaching.